Evaluation of the relationship between cardiac calcification and cardiovascular disease using the echocardiographic calcium score in patients undergoing peritoneal dialysis: a cross-sectional study - Ho-Kwan Sin; Ping-Nam Wong; Kin-Yee Lo; Man-Wai Lo; Shuk-Fan Chan; Kwok-Chi Lo; Yuk-Yi Wong; Lo-Yi Ho; Wing-Tung Kwok; Kai-Chun Chan; Andrew Kui-Man Wong; Siu-Ka Mak (Singapore Medical Journal)
Introduction: An echocardiographic calcium score (ECS) predicts cardiovascular disease (CVD) in the general population. Its utility in peritoneal dialysis (PD) patients is unknown. Methods: This cross-sectional study assessed 125 patients on PD. The ECS (range 0–8) was compared between subjects with CVD and those without. Results: Among the subjects, 54 had CVD and 71 did not. Subjects with CVD were older (69 years vs. 56 years, P < 0.001) and had a higher prevalence of diabetes mellitus (DM) (81.5% vs. 45.1%, P < 0.001). They had lower diastolic blood pressure (72 mmHg vs. 81 mmHg, P < 0.001), lower phosphate (1.6 mmol/L vs. 1.9 mmol/L, P = 0.002), albumin (30 g/L vs. 32 g/L, P = 0.001), parathyroid hormone (34.4 pmol/L vs. 55.8 pmol/L, P = 0.002), total cholesterol (4.5 vs. 4.9, P = 0.047), LDL cholesterol (2.4 mmol/L vs. 2.8 mmol/L, P = 0.019) and HDL cholesterol (0.8 mmol/L vs. 1.1 mmol/L, P = 0.002). The ECS was found to be higher in subjects with CVD than in those without (2 vs. 1, P = 0.001). On multivariate analysis, only DM and age were independently associated with CVD. Conclusion: The ECS was significantly higher in PD patients with CVD than in those without, reflecting a higher vascular calcification burden in the former. It is a potentially useful tool to quantify vascular calcification in PD patients.